(untitled) - Griffin, C. W. (New York, 2006)
This fourth edition covers major advances in design and materials, as well as changes in building codes. It gets you up to speed on roof system performance, emerging materials, drainage, wind uplift, vapor control, fire resistance, thermal insulation, reroofing, and much more. You'll even find field-tested solutions for such problems as lap-seam failures, membrane shrinkage, and fastener backout. Covering all major types of flat, multi-ply, low-slope roofing systems for commercial and industrial facilities, this definitive text also updates you on new procedures in inspection and maintenance.
Keywords: Flat roofs,Roofing,Tấm lợp